THE PREVALENCE OF ANISOMELIA AND NEUROSENSORY IMPAIRMENT AS RISK FACTORS FOR TROPHIC ULCER FORMATION IN DIABETIC PATIENTS - Ivanova, Anna; Melekhovets, Oksana (Eastern Ukrainian Medical Journal, 2025)
Introduction. Diabetic foot ulcers are a major complication of diabetes, often leading to severe outcomes such as lower limb amputation. Risk factors for their formation include vascular disease, microcirculation disorders, impaired tissue regeneration, and local infections. However, the role of leg length discrepancy or anisomelia in combination with peripheral neurosensory deficit as a modifiable risk factor remains underexplored. This study aimed to assess the prevalence of anisomelia and peripheral neuropathy in diabetic patients compared to healthy individuals and analyze their potential impact on trophic ulcer formation. Methods. The study involved 200 participants, including 101 healthy individuals divided by age into two groups and 99 diabetic patients with and without trophic foot ulcers, comparable in age, sex, and body mass index. Anisomelia was measured using a device with a virtual ruler application. Neurosensory impairment was assessed with a modified Neuropathy Disability Score. Data were analyzed using SPSS 27.0, employing Student`s t-tests, Pearson`s chi-square tests, and one-way ANOVA with Bonferroni corrections. Results. The mean values and the distribution of people with different degrees of anisomelia did not differ between students in the final stages of their growth and mature individuals with a developed skeleton (p = 0.232; p = 0.412). There was no statistically significant difference between the mean leg length discrepancy values in patients with diabetes and the healthy population (p = 0.935). The prevalence and severity of anisomelia among patients with diabetes mellitus did not differ significantly from the general population (χ 2 = 2.06; p = 0.356). Neuropathy severity differed significantly between diabetic patients with and without foot ulcers (χ2 = 66.6; p < 0.001), with severe neuropathy predominating in individuals who suffered from trophic ulcers (74.0%). Patients with ulcers had significantly higher NDS scores (8.33 ± 1.76) compared to those without ulcers (4.47 ± 1.07). Conclusions. The study found that leg length discrepancy was similar in prevalence and severity between healthy individuals and diabetic patients. However, even minor asymmetry in people with diabetes may trigger trophic ulcer formation. Peripheral neuropathy severity was significantly higher in diabetic patients with ulcers, suggesting that anisomelia combined with neurosensory impairment may be a key risk factor for diabetic trophic ulceration.